CAR-T IMMUNOTHERAPY IN VARIOUS LYMPHOMAS – AN OVERVIEW INCLUDING THE LATEST STUDIES FROM 2017–2025 - Hanna Pietruszewska,; Oliwia Sędziak,; Sabina Skrzynecka,; Natalia Kruszewska,; Urszula Borucińska, (International Journal of Innovative Technologies in Social Science, 2025)
The review presents the development and current applications of CAR-T (chimeric antigen receptor T-cell therapy) in the treatment of various forms of non-Hodgkin's lymphoma between 2017 and 2025. CAR-T cell immunotherapy, based on the genetic modification of the patient's autologous T cells to recognize the CD19 antigen, has revolutionized the treatment of lymphomas resistant to standard methods. Major clinical trials, such as, have confirmed the high efficacy of CAR-T therapy in patients with relapsed or refractory diffuse large B-cell lymphoma (DLBCL). The complete remission (CR) rates achieved ranged from 40% to 54%, with an acceptable safety profile, mainly including cytokine release syndrome (CRS) and neurotoxicity.In subsequent years, the use of CAR-T was extended to other subtypes of lymphoma. The data collected confirm that CAR-T therapies against CD19 provide high efficacy and durable remissions in numerous types of non-Hodgkin lymphoma, including in treatment-resistant patients. Despite the risks of CRS and neurotoxicity, modern supportive care regimens and improvements in CAR design have improved the safety of the therapy.The conclusions indicate that CAR-T immunotherapy has become a key element in the treatment of lymphoproliferative malignancies, and ongoing research is focused on earlier use of this method, combination therapy with checkpoint inhibitors, and the development of CARs targeting new antigens (CD20, CD22, BCMA).